ANALISIS PENERJEMAHAN GAYA BAHASA METAFORA DALAM NOVEL L’ASSOMMOIR KARYA ÉMILE ZOLA - Aditya, Rhizki Tama (JURNAL ILMU BUDAYA, 2023)
This research has two objectives, are identifying the metaphors in the novel "L'Assommoir" by Émile Zola and "Rumah Minum" translated by Lulu Wijaya, and describing translation procedures metaphors. The method is descriptive qualitative. The data collection uses the basic citation technique, careful reading, and notation using the table.Then, this research uses the basic segmentation of decisive elements and the comparison of different elements. The results indicate that 250 metaphors data are: 53 dead, 48 cliche, 83 standard, 33 recent, 2 adapted, and 31 original. The metaphor translation procedures data include 14 the same image in the TL, 15 replacing SL image with standard TL image, 55 the metaphor by simile (retaining the image), 13 add an image in comparison, 144 conversion metaphor into sense, 4 remove metaphors, and 5 the same image and added descriptive note. In conclusion, the results can generally be used in the process of learning French.